Applying critical literacy theory to examine English Further Education and Training short story textbooks - Sekgobela, Adolph (University of the Witwatersrand, Johannesburg, 2023)
Textbook authors have worked hard over the years to produce quality work. However, it has been a challenge in South African basic education to use these textbooks to train learners to be critical thinkers, which means that learners struggle to cope when they reach higher education. Basic education assesses basic knowledge, without learners themselves being challenged to engage creatively with content and interpret it through a critical lens. This study researched on three short story textbooks, namely Fabulous, Short Story Anthology and Changes using the qualitative method. These are short story textbooks used in public schools in South Africa, as part of English First Additional Language subject content. Purposive sampling was used to make selection of short stories. Within each book, the Department of Basic Education prescribed eight stories for learning. This study selected two of the eight prescribed stories from each book, making six short stories selected for the research. These stories were analysed with their activities against critical literacy theory. It was found that short story activities, especially those studied in Grade 11 and 12, do not assist learners to develop skills such as problem-solving, creative writing, and critical literacy, and that the Grade 10 stories do in some instances promote critical literacy skills development. On the whole, it was found that all short stories limit learners from being creative beings who are able to rewrite, rethink and reconstruct the world around them.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Education (with specialisation in Languages, Literacies and Literatures)to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Post Graduate Bursary Support.
Keywords: Critical literacy theory; Critical thinking; Bloom's taxonomy; English FET; Short story textbooks; Learners' voice; UCTD; SDG-4: Quality education